PENGARUH DEBT TO EQUITY RATIO, SIZE, AUDIT COMMITTEE DILIGENCE, DIVIDEND POLICY PADA PRAKTIK MANAJEMEN LABA - Rikaputri, Putu Shinta Dewanti; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of the debt to equity ratio, capital structure, size, audit committee diligence, and dividend policy of the earnings management practices. Earnings management practices is the act of raising or lowering the profit with a specific purpose. Data analysis technique used is multiple linear regression analysis. The sample selection using purposive sampling nonprobability technique. Research conducted by F test provides results that five variables have a significant influence on earnings management practices. T test showed variable results debt to equity ratio, capital structure, size, audit committee diligence no significant effect on earnings management practices and dividend policy significant negative effect on earnings management practices.
Keywords: Leverage, Size, Audit Committee Diligence, Dividend Policy, Earnings Management